2010
DOI: 10.1590/s0100-55022010000400017
|View full text |Cite
|
Sign up to set email alerts
|

Quiz: um questionário eletrônico para autoavaliação e aprendizagem em genética e biologia molecular

Abstract: O conhecimento sobre temas de Genética e Biologia Molecular, nos últimos anos, vem crescendo de maneira exponencial, demandando constante atualização, principalmente se considerarmos que, ao final do período de graduação, muito desse conhecimento está desatualizado. O Quiz de Genética e Biologia Molecular (GBM) foi proposto como nova ferramenta de ensino para complementar a abordagem dessa temática no ensino de ciências da saúde. Elaborado por alunos dos cursos de Medicina e Sistemas de Informação do UniFOA or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
1
2
0
5
Order By: Relevance
“…The previous organizer is an instructional resource presented at a higher level of abstraction, generality and inclusiveness regarding to the learning material (Moreira, 2013). Some studies corroborate the results found from this experience, considering that they refer to the application of the Quiz in medical teaching practices as a new complementary teaching tool, which can be constantly updated and directed to the difficulties encountered, and it reinforces the idea that educators should consider combining other teaching strategies for knowledge building (Silva, Canedo, Abrantes, Souza, Santos, & Utagawa, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…The previous organizer is an instructional resource presented at a higher level of abstraction, generality and inclusiveness regarding to the learning material (Moreira, 2013). Some studies corroborate the results found from this experience, considering that they refer to the application of the Quiz in medical teaching practices as a new complementary teaching tool, which can be constantly updated and directed to the difficulties encountered, and it reinforces the idea that educators should consider combining other teaching strategies for knowledge building (Silva, Canedo, Abrantes, Souza, Santos, & Utagawa, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…In the area of Tele-genetics, the international literature denotes a growing advancement of studies that encompass actions and practices in Tele-health 10 , 12 , 13 , 28 and with individuals with genetic syndromes 4 . Meanwhile, in the Brazilian literature, Tele-genetics is growing, with studies focused on the medical education of students 24 , education in genetic syndromes, and etiological and social aspects 21 , 22 , among others.…”
Section: Introductionmentioning
confidence: 99%
“…Quiz-type games have already been successfully applied in the medical field for teaching genetics, physiology, and dermatology, among others (4,14,23). In transfusion medicine, e-mails with quizzes (Transfusion News, Question of the Day, https://transfusionnews.com/path-questions/) have been applied for the continuing education of professionals in this area in several countries (15).…”
Section: Discussionmentioning
confidence: 99%